Model Hubungan antara Kepemimpinan Kepala Desa, Modal Sosial, Motivasi dengan Keberdayaan Kader Keluarga Berencana - Juda Julia Kristiarini (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2022)
This study aims to examine the relationship between the variables of village head leadership, social capital, motivation and the empowerment of family planning cadres. The research design is a correlational observational type with a survey approach. The number of research samples was 220 people, which were taken based on proportional cluster random sampling. The data analysis technique used SEM analysis. The results of the study concluded: (1) The leadership of the village head had a direct effect on the empowerment of family planning cadres; (2) The leadership of the village head directly influences the motivation of family planning cadres; (3) Social capital has a direct effect on the motivation of family planning cadres; (4) The motivation of cadres has a direct effect on the empowerment of family planning cadres; (5) Social capital has an indirect effect on the empowerment of family planning cadres which is mediated by the motivation of cadres.